Perancangan dan Implementasi Sistem Informasi Berbasis Website pada Toko Sembako Sayur Amanah - Radhita Rayhan; Ika Nur Fajri (Sekawan Institut, 2025)
In the midst of the rapid development of digital technology, various business sectors, including the trade sector, have begun to adopt digital-based information systems to improve operational efficiency and effectiveness. Toko Sembako Sayur Amanah currently still relies on a manual system for recording transactions, managing stock items, and financial reporting using a cash book. This manual system causes the sales process to be inefficient, time-consuming, and prone to errors such as misrecording or data loss. In addition, the manual system is unable to meet the needs of customers who have limited time and makes it difficult to manage transactions and stock items effectively. To overcome these problems, this research aims to design and implement a website-based information system using the Waterfall method, which includes requirements analysis, system design, implementation, and system testing. Testing is carried out with a Black-box Testing approach to ensure the suitability of system functionality with predetermined needs. The test results show that the developed system has succeeded in increasing the efficiency of managing categories and goods by the admin and making it easier for customers to place orders and make payments online. This research is expected to be a reference for the development of similar systems in other grocery stores with the potential to increase competitiveness in an increasingly competitive market. As a follow-up, this research opens up opportunities for further development, such as integration with mobile applications or more sophisticated inventory management systems.